Semen Characteristics and Protein Contents in SeminalPlasma of Vechur Bulls - Xavier, Sophia; Harshan, Hiron M; C, Jayakumar; Chacko, Leeba; M, Shynu; Kurian, Elizabeth (The Indian Journal of Animal Reproduction, 2024)
The present investigation was carried out to study the semen characteristics of Vechur bulls. A total of 36 ejaculates collected from six Vechur bulls were studied. The overall mean ejaculate volume, colour, pH, mass activity, progressive sperm motility and total seminal plasma protein concentrations were analysed. The mean ejaculate volume noted was 2.26 ± 0.36 mL, colour of semen ranged from milky to thick milky, pH was 6.87 ± 0.02, density from DDD to DDDD, mass activity +++ to ++++ and sperm progressive motility was 78.1 ± 1.05 %. Significant differences in ejaculate volume, mass activity, progressive sperm motility and live sperms were observed among the bulls. The mean protein content of seminal plasma was 84.10 ± 2.73 mg/mL. On SDS-PAGE analysis, 20 proteins bands of varying intensities were observed within the range of 10-180 kDa and preponderance of lower molecular weight proteins was recorded.